Circulating monocytes and B-lymphocytes in neovascular age-related macular degeneration - Hector SM (Dove Medical Press, 2017)
Sven Magnus Hector,1 Torben Lykke Sørensen1,2 1Clinical Eye Research Unit, Zealand University Hospital, Roskilde, 2Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, Denmark Background: Individuals with neovascular age-related macular degeneration (AMD) have altered number and distribution of retinal macrophages and show changes in circulating antibodies. We wanted to investigate the corresponding precursors, with subpopulations. We therefore measured monocyte and B-lymphocyte populations in individuals with neovascular AMD.Design: This was an observational case–control study.Participants or samples: A total of 31 individuals with neovascular AMD and 30 healthy age-matched controls were included.Methods: Patients and controls were interviewed, and ophthalmological examination included visual acuity assessment using the Early Treatment Diabetic Retinopathy Study (ETDRS) chart, spectral domain optical coherence tomography (SD-OCT), slit-lamp examination and fundus photography. Moreover, venous blood was drawn and prepared for flow cytometry. Cells were gated and measured for surface markers.Main outcome measures: Relative amounts of monocytes and B-lymphocytes with subsets, as well as selected surface markers, were measured.Results: The two groups did not significantly differ in age, smoking history, body mass index, physical activity or C-reactive protein (CRP). Total monocytes (percentage of all leukocytes) were lower in the neovascular AMD group (median 5.5%) compared with the level in the control group (6.5%; P-value: 0.028). The percentage of intermediate monocytes positive for cluster of differentiation 11b (CD11b) was lower for AMD patients (99.4%) compared with 100% for the control group (P-value: 0.032).Conclusion: We observed lower numbers of monocytes, which show a potentially impaired ability to migrate across the endothelial wall in patients with neovascular AMD. These subtle changes could potentially lead to an imbalance in the recruitment of macrophages into the retina during disease development. Keywords: macular degeneration, choroidal neovascularization, flow cytometry